2003
DOI: 10.1196/annals.1288.011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and High‐Titer Single Autoantibodies in Schoolchildren Reflecting the Genetic Predisposition for Type 1 Diabetes

Abstract: The study aimed to compare the HLA specificities of AAb-positive healthy schoolchildren with those of patients with type 1 diabetes (T1D). HLA-DRB1 and DQB1 alleles were determined in 178 AAb-positive and 339 AAb-negative schoolchildren aged 6-17 years without first-degree relatives with T1D and in 274 patients with T1D. AAbs against glutamic acid decarboxylase (GADA), protein tyrosine phosphatase (IA-2A), and insulin (IAA) were determined by (125)I-antigen binding, and islet cell cytoplasmic antibodies (ICAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The BABYDIAB study showed that the genetic risk factors found in children who developed multiple islet autoantibodies were absent in children who developed single islet autoantibodies [7,17]. Similarly, the Australian BabyDiab study found that HLA DR4 and DR3 were more prevalent in children who developed persistent multiple islet autoantibodies than in children who were transient or single antibody positive [35], and the Karlsburg schoolchildren study found children with multiple islet autoantibodies, but not those with single islet autoantibodies who had HLA allele frequencies that were similar to those found in T1DM [50]. Finally, high-affinity IAA was associated with high-risk HLA DR4 containing genotypes [27••].…”
Section: Can Genetic Typing Help Stratify T1dm Risk In Autoantibody-pmentioning
confidence: 64%
“…The BABYDIAB study showed that the genetic risk factors found in children who developed multiple islet autoantibodies were absent in children who developed single islet autoantibodies [7,17]. Similarly, the Australian BabyDiab study found that HLA DR4 and DR3 were more prevalent in children who developed persistent multiple islet autoantibodies than in children who were transient or single antibody positive [35], and the Karlsburg schoolchildren study found children with multiple islet autoantibodies, but not those with single islet autoantibodies who had HLA allele frequencies that were similar to those found in T1DM [50]. Finally, high-affinity IAA was associated with high-risk HLA DR4 containing genotypes [27••].…”
Section: Can Genetic Typing Help Stratify T1dm Risk In Autoantibody-pmentioning
confidence: 64%
“…Some of the findings in the NOD mice were similar to what is observed in man. The relationship between increased IAA and more diabetes development is reflected by the faster rate of progression in antibody children if they have an earlier seroconversion or have higher islet autoantibody titers [ 13 , 14 ]. Similar to NOD mice, although much less pronounced, girls with islet autoantibodies progress to diabetes faster than boys [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the Australian BABYDIAB study found that HLA DR4-DQ8 and DR3-DQ2 were more prevalent in children who developed persistent multiple islet autoantibodies than in children who were transient or single antibody positive (21). The Karlsburg schoolchildren study found children with multiple islet autoantibodies, but not in subjects with single islet autoantibodiesthey had HLA allele frequencies that were similar to frequencies found in type 1 diabetes (38). Finally, high affinity IAAs are associated with high-risk HLA DR4-DQ8 containing genotypes (14), and most IA-2A-positive offspring with the HLA DR3-DQ2/DR4-DQ8 or DR4-DQ8/DR4-DQ8 genotypes immediately develop a broad antibody reactivity to multiple epitopes expressed in both IA-2 and IA-2␤ (19).…”
Section: Factors Influencing the Development Of Islet Autoimmunitymentioning
confidence: 88%